Kecanduan Teknologi : Dampak Penggunaan Komputer Terhadap Kesehatan Mental: Penelitian - Muhammad Zulfadli; Kavita Devi Saputri; Nanda Jarti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid development of computer technology has significantly influenced human life in various aspects, including work, education, and entertainment. However, excessive use of computers may lead to technology addiction, which negatively impacts mental health. This study aims to analyze the effects of excessive computer use on individuals’ psychological conditions and identify the factors influencing this relationship. The research employs a Systematic Literature Review (SLR) approach by examining relevant studies and scientific articles. The findings indicate that prolonged computer use can lead to stress, anxiety, depression, and a decline in social interaction skills. Moreover, factors such as self-control, social support, and usage patterns play a vital role in moderating mental health risks. This study highlights the importance of self-regulation and awareness in utilizing technology wisely so that computers can be used effectively without causing adverse effects on users’ psychological well-being.